Wątpliwości na tle usytuowania stosunków rodzinnoprawnych w strukturze grup podatkowych w podatku od spadków i darowizn - Goettel, Mieczysław; Goettel, Aleksy (PRAWO i WIĘŹ, 2025)
The legislator differentiates the assessment of inheritance and gift tax depending on the existence or non-existence of a personal relationship between the acquirer of the property or property right and the person from whom or after whom the acquisition takes place. In this regard, the legislator gives priority to the acquirer who has a legal, family relationship with that person: marriage, kinship, affinity and adoption, placing that acquirer in the first (most privileged) or second tax group. In the context of membership of the above groups, controversies often arise, both in the literature and in practice. These controversies mainly concern spouses who have been legally separated and persons in an adoptive relationship. There are also doubts about the accuracy of the composition of the individual tax groups.